Search for new physics using QUAERO: A general interface to D0 Event data - Abazov, V; Abbott, B; Abdesselam, A; Abolins, M; Abramov, V; Acharya, B; Adams, D; Adams, M; Ahmed, SN; Alexeev, G; Alves, G; Amos, N; et al. (2001)
A method called QUAERO, for automatic optimization of searches for physics beyond the standard model is presented. The method provides a mechanism that allows the availability of high energy collider data. The algorithms used in QUAERO and the final states available for analysis are described. Results showed that the limits obtained on application of the method to standard model and resonant production are comparable to those from previous searches at hadron colliders.